Effect of supplementation with food rich in fatty acids on bovine milk performance and composition - Rodríguez-Molano, Carlos Eduardo; Gómez-Lara, Diego Francisco; Moyano-Bautista, Mónica Andrea (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The effect of supplementation with food rich in fatty acids on bovine milk performance and composition was evaluated. We worked with 15 Holstein cows, multiparous, on the second third of lactation. The animals were divided into control group, group 1 and group 2. We formulated three diets containing 16% crude protein and 1,73 Mcal ENL, and set 7 days for habituation and 83 for trial. We evaluated production (kg), fat (%), protein (%), non-fat solids, lactose (%) and density (g/ml) using the integral Lactoscan® milk analyzer. The diets consist of a staple food and the supplement to try that was added in amounts according to the maximum participation for ruminants. The staple food were alfalfa meal, rice flour, wheat bran, molasses and mineral premix, and the supplements to try were soybean meal and protected fat. We used a completely randomized experimental design and compared the data with the repeated measures ANOVA in R (v. i386). The results show that milk production increased significantly (P =< 0.05) after supplementation wuth soybean meal and fat protected reached in the control group. Although it is possible to increase production (kg/ day), the milk composition parameters did not improve, possibly due to the metabolic abnormality that may occur after ruminal fermentation of fats, and the alteration of the fatty acids mammary synthesis. Keywo